(untitled) - American Medical Association (Hoboken, 2008)
Offering a guide to preventing illness and promoting health, experts from the American Medical Association introduce the foundations of life-long wellness, describing how to prevent such ailments as heart disease, stroke, cancer, hypertension, and diabetes.
Keywords: Health,Medicine, Preventive,Y học, dự phòng,Sức khỏe